VEXAS syndrome: on the threshold of changing perceptions of known diseases - B. D. Chaltsev; A. V. Torgashina; A. M. Lila; T. V. Markova; S. I. Kutsev; O. P. Ryzhkova; A. A. Orlova; A. V. Kokhno; T. I. Solovyova; V. N. Dvirnyk; A. M. Kovrigina; T. N. Obukhova; et al. (Современная ревматология, 2023)
This article presents the first case of VEXAS syndrome identified in the Russian Federation as well as characteristics of currently known clinical manifestations and treatment approaches. The clinical observation described is an impressive example of how the identification of a new pathogenic mutation can change the understanding of the classification, diagnosis and treatment of previously known immunoinflammatory diseases. Thus, in refractory forms of relapsing polychondritis, neutrophilic dermatosis, atypical forms of vasculitis, inflammatory joint diseases or undifferentiated systemic inflammatory syndrome, especially when associated with macrocytic anemia and myelodysplastic syndrome, VEXAS syndrome should be suspected and genetic testing should be performed to exclude the autoinflammatory nature of the existing condition.